Characterization of gaseous nitrogen oxides in the Lower Fraser Valley during Pacific 2001 - Hayden, K. L.; Anlauf, K. G.; Li, S. M.; Macdonald, A. M.; Bottenheim, J. W.; Brook, J. R.; Wiebe, H. A. (ATMOSPHERIC ENVIRONMENT, 2004)
From 13 August-1 September 2001, a number of gaseous chemical compounds were measured at three sites in the Lower Fraser Valley, British Columbia: (1) Slocan-in the city of Vancouver; (2) Langley-in a rural, agricultural area about 35 km southeast of Vancouver; and (3) Sumas-about 65 km inland on a forested mountain (300m asl). Although the Langley and Sumas sites were located away from major emission sources, CO, NOx and NOy mixing ratios indicate that these sites were often impacted by anthropogenic emissions. At Langley and Slocan, NO and CO mixing ratios were highest between 0400-0700 PDT (UT=PDT-8h) due to the buildup of fresh vehicular emissions under a nocturnal inversion. At the elevated Sumas site, during the growth of the boundary layer, upward mixing of fresh emissions was observed, delayed by 3 h compared to the other two sites. NOx was the largest component of NOy at Langley and Sumas, averaging 75-80%. At Langley, the HNO3 fraction of NOy during the afternoon ranged from 15% to 28%, compared to <10% at the other two sites. PAN was significantly lower than HNO3 at <5% of NOy at all three sites. The sum of all individual nitrogen oxide species, SigmaNO(yi) accounted for 85% and 93% of NOy on average at Langley and Sumas, respectively. The chemical age was estimated at the three sites using the ratio (HONO+HNO3+PAN)/NOy. The daytime (1400-1800 PDT) ratios at Langley (0.19-0.40) were higher than those at either Slocan (0.04-0.12) or Sumas (0.09-0.19), mainly driven by higher HNO3 contributions to NOy. The higher ratios at Langley suggest that the extent of processing in air masses at the site during the daytime was greater than at Slocan or Sumas. At Sumas, the elevated nighttime ratios (0.05-0.29) were attributed to transport of more aged air masses to the site and the contribution of HNO3 from N2O5 hydrolysis. O-3 was only weakly correlated with the oxidation products of NOx at Langley (m = 2.5 +/- 9.1) and Sumas (m = 7.3 +/- 8.2). Meteorological conditions (lower radiation levels, cooler temperatures) were not favourable for photochemical pollutant processing. The dominant NOx fraction of NOy (see Section 3.2.1) clearly shows that most of the oxidized nitrogen remained in the form of NOx with very limited chemical processing and relatively low O-3 levels. Crown Copyright (C) 2004 Published by Elsevier Ltd. All rights reserved.